Problems of Evaluating Frameworks for Web Applications - Bieliaiev, Oleksandr; Selivorstova, Yuliia; Liutenko, Irina (My University, 2021)
In the process of creating software, the task of choosing the best framework in this case often arises, for which it is necessary to evaluate the frameworks. The work considered the features of the frameworks that are used in web development. Criteria for the rationality of using frameworks for developing web applications are given. The components of front-end development are considered and the classification of frameworks is given. It is proposed to evaluate frameworks using the ISO / IEC 25010 quality model. The main functionality of front-end frameworks, which are used for evaluation, are formulated. Such methods as the synthesis of a formal decision-making model, qualimetry, SACS, analysis of variance, and factor analysis can be used to evaluate frameworks. Subsequently, to evaluate the frameworks, the SACS method was chosen as the best methodology for multi-criteria selection.
Keywords: Evaluation; quality; software; criterion; assessment methods; front-end; ISO 25010